Adopsi Inovasi Produk Polybag Ramah Lingkungan (Poraling) untuk Usaha Pembibitan Tanaman Hortikultura dan Perkebunan di Kota Banda Aceh - Syafruddin; Yusnizar; Nurahmi, Erida; Iskandar, Elvira (JURNAL PENGABDIAN PEMBANGUNAN PERTANIAN DAN LINGKUNGAN (JP3L), 2024)
The knowledge and skills of the Horticultural Plant Nursery and Plantation Business Partner Group in the Banda Aceh area regarding assembling environmentally friendly polybags are still limited. The aim of this Product-Based Community Service activity is to increase the knowledge and skills of the Kopelma Darussalam and LA Garden Banda Aceh Nursery Business Group in assembling and using environmentally friendly polybags. The main obstacle in increasing the production of various plant nurseries is the high price of polybags or containers for seedlings, which are not durable and are not environmentally friendly. The implementation of this activity includes counseling and demonstrations on the assembly and use of environmentally friendly polybags for breeding horticultural and plantation plants. The target and output of this activity is to increase the knowledge and skills of partner groups regarding techniques for making and using environmentally friendly polybags. It is hoped that this activity can produce 500 units of environmentally friendly polybags per production. Another outcome is that partner groups can increase income in the horticultural plant nursery and plantation business through the use of environmentally friendly polybags. The results of the service have succeeded in assembling environmentally friendly polybags which are used for breeding horticultural and plantation plants. Seedlings produced by planting using poraling show very good results or grow one hundred percent on average. The target group has been able to use poraling sustainably in its breeding business.